Cutaneous epithelioid haemangiomas show somatic mutations in the mitogen‐activated protein kinase pathway. (1st March 2022) - Maurus, K.; Kosnopfel, C.; Kneitz, H.; Appenzeller, S.; Schrama, D.; Glutsch, V.; Roth, S.; Gerhard‐Hartmann, E.; Rosenfeldt, M.; Möhrmann, L.; Fröhlich, M.; Hübschmann, D.; et al.
Summary: Background: Epithelioid haemangioma (EH) arising from the skin is a benign vascular tumour with marked inflammatory cell infiltration, which exhibits a high tendency to persist and frequently recurs after resection. So far, the underlying pathogenesis is largely elusive. Objectives: To identify genetic alterations by next‐generation sequencing and/or droplet digital polymerase chain reaction (ddPCR) in cutaneous EH. Methods: DNA and RNA from an EH lesion of an index patient were subjected to whole‐genome and RNA sequencing. Multiplex PCR‐based panel sequencing of genomic DNA isolated from archival formalin‐fixed paraffin‐embedded tissue of 18 patients with cutaneous EH was performed. ddPCR was used to confirm mutations. Results: We identified somatic mutations in genes of the mitogen‐activated protein kinase (MAPK) pathway ( MAP2K1 and KRAS ) in cutaneous EH biopsies. By ddPCR we could confirm the recurrent presence of activating, low‐frequency mutations affecting MAP2K1 . In total, nine out of 18 patients analysed showed activating MAPK pathway mutations, which were mutually exclusive. Comparative analysis of tissue areas enriched for lymphatic infiltrate or aberrant endothelial cells, respectively, revealed an association of these mutations with the presence of endothelial cells. Conclusions: Taken together, our data suggest that EH shows somatic mutations in genes of the MAPK pathway which might contribute to the formation of this benign tumour.